Isolation and Identification of Microorganisms Associated With Yoghurt Enriched With Coconut Milk During Refrigerated Storage - Obasi, Blessing Chidi; Uluocha, Blessing Emmanuel (Kwaghe International Journal of Sciences and Technology, 2025)
Current trends and evolving consumer preferences present significant opportunities for innovation in fermented dairy products. This study investigated the microbial flora associated with yoghurt enriched with coconut milk during refrigerated storage. Yoghurt samples were produced by blending 800 g of reconstituted powdered cow milk with six litres of water, followed by the addition of coconut milk in varying proportions (10%, 20%, 30%, and 40%), alongside a control sample made with 100% cow milk. After fermentation, all samples were stored under refrigeration for two weeks. Microbiological analysis showed no bacterial growth at week zero in any sample. However, viable bacterial counts emerged in weeks one and two, ranging from 3.0×10³ to 5.0×10³ cfu/ml and 5.3×10³ to 11.2×10³ cfu/ml, respectively. Yeast and mold counts ranged from 2.6×10³ to 4.0×10³ cfu/ml in week one and 3.6×10³ to 5.8×10³ cfu/ml in week two. Coliform bacteria were not detected in any sample throughout the storage period. Bacterial isolates identified included Escherichia coli, Staphylococcus aureus, Enterobacter aerogenes, Staphylococcus epidermidis, and Klebsiella pneumoniae. Fungal isolates comprised Aspergillus spp., Fusarium spp., Candida spp., and Saccharomyces spp. The study concludes that yoghurt enriched with coconut milk can serve as a vehicle for probiotic delivery, offering enhanced nutritional benefits and contributing to consumer health and well-being.